Renal and cardiac effects of the PDE9 inhibitor BAY 73-6691 in 5/6 nephrectomized rats - Chen, Xin; Delić, Denis; Cao, Yaochen; Zhang, Zeyu; Wu, Hongwei; Hasan, Ahmed A.; Gaballa, Mohamed M. S.; Yin, Lianghong; Krämer, Bernhard; Klein, Thomas; Shi, Xin; He, Ben; et al. (Pflügers Archiv, 2024)
It has been suggested that the novel selective phosphodiesterase 9 (PDE9) inhibitor may improve cardiac and renal function by blocking 3′,5′-cyclic guanosine monophosphate (cGMP) degradation. 5/6 nephrectomized (5/6Nx) rats were used to investigate the effects of the PDE9 inhibitor (BAY 73-6691) on the heart and kidney. Two doses of BAY 73-6691 (1 mg/kg/day and 5 mg/kg/day) were given for 95 days. The 5/6Nx rats developed albuminuria, a decrease in serum creatinine clearance (Ccr), and elevated serum troponin T levels. Echocardiographic data showed that 5/6 nephrectomy resulted in increased fractional shortening (FS), stroke volume (SV), and left ventricular ejection fraction (EF). However, 95 days of PDE9 inhibitor treatment did not improve any cardiac and renal functional parameter. Histopathologically, 5/6 nephrectomy resulted in severe kidney and heart damage, such as renal interstitial fibrosis, glomerulosclerosis, and enlarged cardiomyocytes. Telmisartan attenuated renal interstitial fibrosis and glomerulosclerosis as well as improved cardiomyocyte size. However, except for cardiomyocyte size and renal perivascular fibrosis, BAY 73-6691 had no effect on other cardiac and renal histologic parameters. Pathway enrichment analysis using RNA sequencing data of kidney and heart tissue identified chronic kidney disease pathways, such as phosphatidylinositol 3-kinase (PI3K)—protein kinase B (Akt) signaling pathway, complement and coagulation cascades, and nuclear factor kappa B (NF-κB) signaling pathway. PDE9i did not affect any of these disease-related pathways. Two dosages of the PDE9 inhibitor BAY 73-6691 known to be effective in other rat models have only limited cardio-renal protective effects in 5/6 nephrectomized rats.
Gesehen am 21.06.2024